Perennial rice varieties for irrigated rice system in the Sahel - CGIAR Research Program on Rice (2021)
The agronomic performance of five perennial rice varieties was evaluated on-station under different cropping systems. Results showed that under both cropping systems, the most promising perennial variety was PR 107, which had a higher annual cumulative yield of 1.1 t/ha (10%) than Sahel 108 (the most common variety used).